Adopting a flipped classroom approach for teaching molar calculations to biochemistry and genetics students. Issue 3 (30th December 2019) - Francis, Nigel; Morgan, Alwena; Holm, Sean; Davey, Ross; Bodger, Owen; Dudley, Ed
Abstract: The flipped classroom is a relatively new active learning pedagogical intervention, gaining popularity as a blended learning methodology. The flipped classroom comprises two distinct parts, directed learning carried out at the student's own pace away from the classroom and an interactive, class‐based activity encouraging problem‐solving and experiential learning. This research presents a 1‐year study to measure student performance and perception toward a flipped classroom approach to teaching core biochemical calculations to first‐year undergraduate biochemistry and genetics students. A post‐task questionnaire showed an overall positive student perception with an associated significant improvement in the end of module summative assessment. These results suggest that this teaching approach offers some advantages over more traditional teaching pedagogies.